2014
DOI: 10.1002/pssa.201330309
|View full text |Cite
|
Sign up to set email alerts
|

A giant magnetoimpedance sensor for sensitive detection of streptavidin‐coupled Dynabeads

Abstract: An integrated giant magnetoimpedance (GMI) sensor has been used for the detection of Dynabeads® MyOne Streptavidin C1 (DMS). An Au film was sputtered onto magnetic sensing elements for the immobilization of DMS in order to develop an integrated biosensor for potentially biomedical applications. The GMI responses were measured for the detection of DMS from 0.1 µg mL−1 to 100 µg mL−1. We observed that the GMI effect was greatly improved at high frequencies owing to the presence of superparamagnetic beads. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
(93 reference statements)
2
11
1
Order By: Relevance
“…If a cluster of magnetic beads forms, the adjacent magnetic fields produced by the beads would cancel each other out, resulting in a lower magnetic signal. A similar finding is shown in Figure 7c,d, where the lowest Dynabead concentration (0.1 µg/mL) shows the highest MI effect [113]. They also observed that when Dynabeads were unevenly distributed at concentrations of 1 µg/mL the MI was reduced.…”
Section: Effect Of Magnetic Particle Accumulation On MI Responsesupporting
confidence: 84%
See 3 more Smart Citations
“…If a cluster of magnetic beads forms, the adjacent magnetic fields produced by the beads would cancel each other out, resulting in a lower magnetic signal. A similar finding is shown in Figure 7c,d, where the lowest Dynabead concentration (0.1 µg/mL) shows the highest MI effect [113]. They also observed that when Dynabeads were unevenly distributed at concentrations of 1 µg/mL the MI was reduced.…”
Section: Effect Of Magnetic Particle Accumulation On MI Responsesupporting
confidence: 84%
“…They also observed that when Dynabeads were unevenly distributed at concentrations of 1 μg/mL the MI was reduced. This reduction in MI is assumed to be due to non-uniform distribution and high-level clusters beads [ 113 ]. Comparable findings have been reported, where large MI responses have been achieved at low concentrations [ 111 , 114 , 115 ].…”
Section: Magnetic Particle Concentration and Magnetic Field Influementioning
confidence: 99%
See 2 more Smart Citations
“…Currently, a novel graphene nanomaterial, namely core‐shell magnetic graphitic nanocapsule (MGN), has been developed, which inherits the superior quenching ability of graphene and magnetic separation property of magnetic nanoparticles . The excellent properties of MGN show great potential in nucleic acid detection, cell enrichment, and electrochemical analysis.…”
Section: Introductionmentioning
confidence: 99%